2009
DOI: 10.1007/s00442-009-1489-4
|View full text |Cite
|
Sign up to set email alerts
|

Deviation from strict homeostasis across multiple trophic levels in an invertebrate consumer assemblage exposed to high chronic phosphorus enrichment in a Neotropical stream

Abstract: A central tenet of ecological stoichiometry is that consumer elemental composition is relatively independent of food resource nutrient content. Although the P content of some invertebrate consumer taxa can increase as a consequence of P-enriched food resources, little is known about how ecosystem nutrient loading can affect the elemental composition of entire consumer assemblages. Here we examine the potential for P enrichment across invertebrate consumer assemblages in response to chronic high P loading. We m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
129
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(135 citation statements)
references
References 38 publications
4
129
2
Order By: Relevance
“…During the recovery process many plant species become mature and start flowering and fruiting which attract insects (bees, wasps, butterflies, moths, beetles and flies) which is a major diet of avian species. Invertebrate communities of the tropical rain forest are highly diverse and their distribution and richness is associated with a diversity of vegetation structure and composition such as foliage, flowers, fruits, barks (Small and Pringle, 2010;Batista Matos et al, 2013;Peters et al, 2013). Silva and Brandao (2010) reported that invertebrate density strongly associated with vegetation structure and may vary at spatial scales of a few meters.…”
Section: Discussionmentioning
confidence: 99%
“…During the recovery process many plant species become mature and start flowering and fruiting which attract insects (bees, wasps, butterflies, moths, beetles and flies) which is a major diet of avian species. Invertebrate communities of the tropical rain forest are highly diverse and their distribution and richness is associated with a diversity of vegetation structure and composition such as foliage, flowers, fruits, barks (Small and Pringle, 2010;Batista Matos et al, 2013;Peters et al, 2013). Silva and Brandao (2010) reported that invertebrate density strongly associated with vegetation structure and may vary at spatial scales of a few meters.…”
Section: Discussionmentioning
confidence: 99%
“…For example, zooplankton C:P ratio is strongly correlated to the seston C:P ratio (Hessen et al, 2005). A field study also found that invertebrates across multiple trophic levels in the high-P stream had significantly higher P content and lower C:P compared to the low-P stream (Small and Pringle, 2010). That study found that between-stream variation in P content of a given taxon greatly exceeds in-stream variation among different taxa.…”
Section: Introductionmentioning
confidence: 91%
“…To date, studies of organismal stoichiometry have mostly focused on characterizing variability and drivers among taxonomic and functional groups (Cross et al, 2003;Evans-White et al, 2005;Small and Pringle, 2010). In contrast, relatively few studies have examined the extent and causes of intraspecific variability in organismal stoichiometry in natural ecosystems .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, oil-based and polyphenolic substances contained in mesophyll cells Grac¸a, 1995, 1999;Canhoto et al, 2002) act as barriers to fungal colonization and shredder consumption, leading to altered detritus processing and shredding activity Abelho and Grac¸a, 1996;Pozo et al, 1998;Lo´pez et al, 2001) and thus, the structure and functioning of forested headwater streams. There are many studies that have demonstrated how stream invertebrates may evolve developmental adaptations for the utilization of available resources (Rowe and Ludwig, 1991) and/or change their internal elemental ratios in response to resource quality (Cross et al, 2003;Small and Pringle, 2010). These responses are manifested at the physiological, behavioural or genetic level and depend on individual requirements (Slansky and Scriber, 1985;Sterner and Elser, 2002;Swan and Palmer, 2006).…”
Section: Introductionmentioning
confidence: 99%